Local Theories and Bohmian Mechanics - Syros, C. (HNPS Advances in Nuclear Physics, 2020)
One of the last develoonents in the research for extending the scope of the quantum theory is the recently appearing work on the Bohmian Mechanics. The motivation for an extension is provided by the conclusions of the EPR paradoxon and the famous alternative concerning the physical reality. Discussed are some properties of Bohmian Mechanics concerning the self-consistency of the theory.